Sprechen und Erzählen beim Stricker Kommunikative Formate in mittelhochdeutschen Kurzerzählungen - Nowakowski, Nina (Trends in Medieval Philology, 2018)
This study traces the poetics and narrative style of the Stricker's epics back to the communicative pragmatics of their time. It analyzes depictions of counselling, dispute, and religious speech using approaches from communication theory, narratology, and the history of mediality. In this way, the study links a new interpretation of the Middle High German short story with ideas about the methods of literary theory.